The Gumelnița culture settlements in the Prut-Dniester Rivers area, in light of old and new research from Taraclia I (Republic of Moldova) - Mistreanu, Eugeniu; Przybyła, Marcin M. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The discovery of the first Gumelniţa Culture settlements in the region between the Prut and the Dniester Rivers dates back to the 1960s and 1970s. Currently, thirty three settlements of this culture are known in the territory of Ukraine and Moldova. One of them, representing the Stoicani-Aldeni of Gumelniţa Culture variant, is located in Taraclia (Taraclia district, Republic of Moldova). It has been excavated since 1979. In the spring of 2018, magnetic research was carried out on the site. They revealed the presence of a fortification system surrounding an area of approximately 1.7 hectares. It consisted of two parallel ditches forming a quadrangular arrangement. Similar fortifications have been discovered on sites belonging to the Gumelniţa- Kodjadermen-Karanovo VI cultural complex, located in the South-Eastern European region.
Keywords: Eneolithic; Gumelniţa-Kodjadermen-Karanovo VI cultural complex; Gumelniţa culture; enclosure; fortified settlement